(untitled) (Scientific journal of the Fergana State University, 2025)
High production rates, low plastic recycling levels, and the long lifespan of plastics have led to significant accumulation of the material in the environment. This includes plastic fragments <5 mm, commonly referred to as microplastics (MPs). Currently, the greatest focus is on studying polymer particles in aquatic environments, with significantly fewer studies dedicated to soil. However, the content of MPs in soil ecosystems can be 4-23 times higher than in seawater, with the most significant contamination occurring in agricultural and urban areas. Data suggests that MPs can significantly alter the physical and chemical properties of soil (pH, organic matter content, water-holding capacity, bulk density, etc.) and negatively impact reproduction, growth, nutritional characteristics, and survival of the entire spectrum of soil biota. This article examines the main consequences of introducing various MP polymers into the soil and outlines promising directions for future research.